2005
DOI: 10.1302/0301-620x.87b4.15555
|View full text |Cite
|
Sign up to set email alerts
|

Crystal arthropathy of the lumbar spine

Abstract: There have been very few reports in the literature of gout and pseudogout of the spine. We describe six patients who presented with acute sciatica attributable to spinal stenosis with cyst formation in the facet joints. Cytopathological studies confirmed the diagnosis of crystal arthropathy in each case. Specific formation of a synovial cyst was identified pre-operatively by MRI in five patients. In the sixth, the diagnosis was made incidentally during decompressive surgery. Surgical decompression alone was un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 21 publications
2
19
0
2
Order By: Relevance
“…There were degenerative changes in our case, consistent with her age, and it was thought that this could contribute to the formation of spinal tophus. Crystal deposition is generally seen in the vertebral bodies in the spine, pedicles, lamina, ligamentum flavum, interapophyseal cartilage, intervertebral disc and epidural space [1,10,15]. In our case also, there were vertebral body, pedicle and neural foramen involvements.…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…There were degenerative changes in our case, consistent with her age, and it was thought that this could contribute to the formation of spinal tophus. Crystal deposition is generally seen in the vertebral bodies in the spine, pedicles, lamina, ligamentum flavum, interapophyseal cartilage, intervertebral disc and epidural space [1,10,15]. In our case also, there were vertebral body, pedicle and neural foramen involvements.…”
Section: Discussionsupporting
confidence: 58%
“…Kelly et al [7] have reported that all the sections of the spine are equally involved in gout patients. While the most frequent involvement in the cases reported in the literature is the lumbar region, especially L4-5 region, furthermore thoracic and cervical region involvements are also seen [1,4,10]. Lumbar region involvement was present in our case.…”
Section: Discussionsupporting
confidence: 42%
See 3 more Smart Citations